Marketing Strategies Education Oriented Market, Customers And Advantages Competitive - Elvi Rahmi, Moh. Zaini, Moh. Muslim, Imam Junaris (Journal of Education and Teaching Learning, 2021)
Marketing of educational services is a strategy undertaken by the agency in improving human resources are in an institution, with the aim to improve the image of the institution of quality education and can compete with other educational institutions, as well as able to boost high competitiveness. This also shows that competition in the world of education is unavoidable, seeing that many educational institutions have been abandoned by their customers so that in recent years there have been mergers between educational institutions. Besides, the ability of administrators is a prerequisite in maintaining and improving educational institutions. Based on this, there are several problems that must be achieved by Islamic educational institutions, especially schools to market the services of these educational institutions with the aim of Islamic educational institutions being more widely known among the public as consumers of educational services.